Nutritional status of elderly and its association with frailty among them - Deshpande, Amit Vasant; Ravikumar, Baer Philip (International Journal Of Community Medicine And Public Health, 2021)
Background: Malnutrition among geriatrics remain undetected. The present study was conducted to assess the prevalence of malnutrition among geriatric outpatients and various factors associated with it. Methods: This cross-sectional study was done in Mamata medical college, Khammam, Telangana, in which we included geriatric patients (more than 60 years of age) who visited the outpatient clinic between January 2021 till March 2021. All study participants were evaluated for the following two domains of frailty: physical frailty and psychological frailty. Results: During the study period, we included 185 participants in the study. Based on mini nutritional assessment (MNA), 20% participants had normal nutrition, 55% were at risk of malnutrition and 25% had malnutrition. We observed that 59% of the participants with malnutrition were aged more than 80 years, 35% were smokers, 67% were living alone and 83% had comorbidities. It was observed that 67% and 57% of the study participants with malnutrition had impaired activities of daily living and impaired instrumental activities of daily living respectively. 54% of those malnutrition were depressed, which was significantly higher as compared to those with normal nutrition and those at risk of malnutrition (p value <0.05). Conclusions: The results of the present study demonstrate the nutritional status of geriatric outpatients is associated with physical as well as psychological frailty. Therefore, it is recommended that detailed nutritional assessment of patients of geriatric age groups should be conducted when they present in the outpatient clinic for any reason or complaint.